The control of translational accuracy is a determinant of healthy ageing in yeast. Issue 1 (January 2017) - von der Haar, Tobias; Leadsham, Jane E.; Sauvadet, Aimie; Tarrant, Daniel; Adam, Ilectra S.; Saromi, Kofo; Laun, Peter; Rinnerthaler, Mark; Breitenbach-Koller, Hannelore; Breitenbach, Michael; Tuite, Mick F.; Gourlay, Campbell W.
Abstract : Abstract : Life requires the maintenance of molecular function in the face of stochastic processes that tend to adversely affect macromolecular integrity. This is particularly relevant during ageing, as many cellular functions decline with age, including growth, mitochondrial function and energy metabolism. Protein synthesis must deliver functional proteins at all times, implying that the effects of protein synthesis errors like amino acid misincorporation and stop-codon read-through must be minimized during ageing. Here we show that loss of translational accuracy accelerates the loss of viability in stationary phase yeast. Since reduced translational accuracy also reduces the folding competence of at least some proteins, we hypothesize that negative interactions between translational errors and age-related protein damage together overwhelm the cellular chaperone network. We further show that multiple cellular signalling networks control basal error rates in yeast cells, including a ROS signal controlled by mitochondrial activity, and the Ras pathway. Together, our findings indicate that signalling pathways regulating growth, protein homeostasis and energy metabolism may jointly safeguard accurate protein synthesis during healthy ageing.